The Yemen Model Why U.S. Policy Has Failed in the Middle East - Stark, Alexandra (Yale University Press, 2024)
A close look at failed U.S. policies in the Middle East, offering a fresh perspective on how best to reorient goals in the region In this book Alexandra Stark argues that the U.S. approach to Yemen offers insights into the failures of American foreign policy throughout the Middle East. Stark makes the case that despite often being drawn into conflicts within Yemen, the United States has not achieved its policy goals because it has narrowly focused on counterterrorism and regional geopolitical competition rather than on the well-being of Yemenis themselves. She offers recommendations designed to reorient U.S. policy in the Middle East in pursuit of U.S. national security interests and to support the people of these countries in their efforts to make their own communities safe, secure, and prosperous